Umowa jako prawna forma działania administracji publicznej w polskiej i niemieckiej doktrynie prawa publicznego - Sancewicz, Paweł (Wydawnictwo naukowe UAM, 2019)
Within the administrative construction of legal forms of public administration activity developed by the doctrine of administrative law, one may distinguish both a civil-law contract (private-law), as well as an agreement having certain features of a public-law contract. The German doctrine of public law, has long been struggling with problems of legal qualification of contracts used as legal forms of action by public administration entities. As part of the work undertaken by the German doctrine of public law, a two step theory, a concept of contract law in administration and a model administrative contract have been developed. Approximation of these theories allowed the Polish doctrine of public law to identify the most important features, which should characterise the theoretical construction of a public-law contract concluded with a citizen or an administrative contract. First of all, it should be concluded by a public administration entity on the basis of its competence. The administrative agreement should concern the relationship between the administration and the citizens. Secondly, the subject matter of the contract should be governed by public law and relate exclusively to the performance of public administration tasks. Thirdly, disputes arising from an administrative agreement should be submitted to the jurisdiction of administrative courts. The article shows that from the point of view of legal protection of the individual this is a crucial matter. Although the legislator has not decided to introduce an administrative agreement into the Polish legal system, many of the contracts already in operation under Polish law have certain features which at least in part resemble the administrative agreement described above. Such an administrative agreement often concerns the relationship between public administration and the citizen and is concluded in connection with the performance of public tasks. De lege ferenda the conclusion of an administrative contract should be subject to review by the administrative courts.
Agreement as a legal form of operation of public administration in Polish and German doctrine of public law
Keywords: legal forms of operation; administrative agreement; contract law in administration; general provisions of administrative law